Epitope mapping of SARS-CoV-2 spike protein differentiates the antibody binding activity in vaccinated and infected individuals - Felbinger, Nathaniel; Trudil, David; Loomis, Lawrence; Ascione, Richard; Siragusa, Gregory; Haba, Seiji; Rastogi, Shruti; Mucci, Aidan; Claycomb, Mark; Snowberger, Sebastian; Luke, Brian; Francesconi, Stephen; et al. (Frontiers in Virology, 2023)
Previous studies have attempted to characterize the antibody response of individuals to the SARS-CoV-2 virus on a linear peptide level by utilizing peptide microarrays. These studies have helped to identify epitopes that have potential to be used for diagnostic tests to identify infected individuals. The immunological responses of individuals who have received the two most popular vaccines available in the US, the Moderna mRNA-1273 or the Pfizer BNT162b2 mRNA vaccines, have not been characterized. We aimed to identify linear peptides of the SARS-CoV-2 spike protein that elicited high IgG or IgA binding activity and to compare the immunoreactivity of infected individuals to those who received both doses of either vaccine by utilizing peptide microarrays. Our results revealed peptide epitopes of significant IgG binding among recently infected individuals. Some of these peptides are located near variable regions of the receptor binding domains as well as the conserved region in the c-terminal of the spike protein implicated in the high infectivity of SARS-CoV-2. Vaccinated individuals lacked a response to these distinct markers despite the overall antibody binding activity being similar.